Biocontrol of ochratoxigenic fungi by endogenous lactic acid bacteria and yeasts from ivorian robusta coffee in the context of climate change - López Rodríguez, Claudia (Cranfield University, 2023)
This doctoral research delves into the innovative domain of biocontrol strategies targeting mycotoxigenic fungi in the context of climate change. Focusing on Ivorian coffee, a vital economic and agricultural commodity, the study explores the potential of indigenous lactic acid bacteria (LAB) and yeasts as biocontrol agents. Mycotoxins, toxic secondary metabolites produced by fungi, pose significant health risks and economic losses. As climate change amplifies the proliferation of mycotoxigenic fungi, the demand for sustainable and eco-friendly interventions intensifies. The research encompasses comprehensive isolation, identification, and characterization of LAB and yeasts from Ivorian coffee, evaluating their antagonistic properties against mycotoxigenic fungi. Furthermore, the study elucidates the mechanisms underlying the biocontrol activity, shedding light on how these microorganisms mitigate mycotoxin contamination. This research is pivotal in the pursuit of climate-resilient strategies for mycotoxin management, contributing to both food safety and agricultural sustainability.
Verheecke-Vaessen, Carol - Associate Supervisor Fontana, Angelique - Associate Supervisor Strub, Caroline - Associate Supervisor
Keywords: biocontrol; mycotoxins; lactic acid bacteria; yeasts; detoxification; metabarcoding